MOTIVASI SISWA-SISWI DALAM MENGIKUTI KEGIATAN EKSTRAKURIKULER DRUM BAND (STUDI PADA SMP NEGERI 11 SURABAYA) - RIZKY SAIFUDIN SANTASA, MUHAMMAD (Jurnal Kesehatan Olahraga, 2016)
Motivation is something push someone to do something for specially achievement. There are two kinds of motivation intrinsic and extrinsic motivation. Intrinsic motivation points to activity for enjoyment and satisfaction. While extrinsic motivation is wondered to show because of reward from outside of them selves. Both of them is needed in extracurricular activity. One of the extracurricular activity get more attention of the researcher in SMP Negeri 11 Surabaya is drum band. Because of data are available, there are decrease in the number of participant drum band extracurricular activity. In 2014-2015, there was 70 male and female students, there are 44 male and 26 female followed this extracurricular, but in 2015-2016 there is only 37 students follow this activity there are 24 males and 13 females with 12-13 years old.. The researcher aim of this research is eager to motivation level (intrinsic and extrinsic) belongs of the students in SMP Negeri 11 Surabaya. The researcher uses quantitative descriptive method. The researcher also uses closed questionnaire it was given to the participants of drum band extracurricular activity. The data is gotten and processed with likert scale. Based on result of data analysis is done to answer formulation problem. The researcher gets the result of calculation of average percentage of every dimension indicator. Intrinsic dimention with total average percentage 73,04% include high category. Extrinsic dimention with total average percentage 64,36% include high category. Both of two total averages dimension is 68,7% include high category. Finally the researcher gets conclution that the students motivation level in SMP Negeri 11 Surabaya to follow drum band extracurricular activity is high. It has proven and include high category. Key Words: Motivation, Intrinsic and Extrinsic, Drum Band